Comparison of Small Incision Lenticule Extraction (SMILE) and Femtosecond Laser In-Situ Keratomileusis (F-LASIK) for the Correction of Myopia and Astigmatism: 1-Year Clinical Outcome - Marianne Roque, MD; Ruben Lim Lim Bon Siong, MD; Irwin Cua, MD; Bernardo Joaquin P. Tuano, MD; Winston Villar, MD (Philippine Journal of Ophthalmology)
Objective: To compare the efficacy, refractive predictability, stability and safety of Small Incision Lenticule Extraction (SMILE) and Femtosecond Laser In-Situ Keratomileusis (F-LASIK) for the correction of myopia and astigmatism.